An All‐Scale Hierarchical Architecture Induces Colossal Room‐Temperature Electrocaloric Effect at Ultralow Electric Field in Polymer Nanocomposites. Issue 30 (21st June 2020) - Chen, Yuqi; Qian, Jianfeng; Yu, Jinyao; Guo, Mengfan; Zhang, Qinghua; Jiang, Jianyong; Shen, Zhonghui; Chen, Long‐Qing; Shen, Yang
Abstract: Composed of electrocaloric (EC) ceramics and polymers, polymer composites with high EC performances are considered as promising candidates for next‐generation all‐solid‐state cooling devices. Their mass application is limited by the low EC strength, which requires very high operational voltage to induce appreciable temperature change. Here, an all‐scale hierarchical architecture is proposed and demonstrated to achieve high EC strength in poly(vinylidene fluoride‐trifluoroethylene‐chlorofluoroethylene)‐based nanocomposites. On the atomic scale, highly polarizable hierarchical interfaces are induced by incorporating BiFeO3 (BFO) nanoparticles in Ba(Zr0.21 Ti0.79 )O3 (BZT) nanofibers (BFO@BZT_nfs); on the microscopic scale, percolation of the interfaces further raises the polarization of the composite nanofibers; on the mesoscopic scale, orthotropic orientation of BFO@BZT_nfs leads to much enhanced breakdown strength of the nanocomposites. As a result, an ultrahigh EC strength of ≈0.22 K m MV −1 is obtained at an ultralow electric field of 75 MV m −1 in nanocomposites filled with the orthotropic composite nanofibers, which is by far the highest value achieved in polymer nanocomposites at a moderate electric field. Results of high‐angle annular dark‐field scanning transmission electron microscopy, in situ scanning Kelvin probe microscopy characterization, and phase‐field simulations all indicate that the much enhanced EC performances can be attributed to the all‐scale hierarchical structures of the nanocomposite. Abstract : An all‐scale hierarchical approach to achieving ultrahigh electrocaloric (EC) strength in flexible polymer composites is proposed and demonstrated. The enhanced EC performance is mainly attributed to the hierarchical interfaces inside the composite nanofibers. In addition, the orthotropic configuration of the BFO@BZT_nfs inside the terpolymer matrix further increases E b of the nanocomposite and leads to substantially enhanced EC strength under a moderate electric field.